2018
DOI: 10.1039/c7ra12997a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation of phenol in a novel cyclic activated sludge integrated with a rotating bed bioreactor in anoxic and peroxidase-mediated conditions

Abstract: Cyclic activated sludge integrated with a rotating bed bioreactor (CASIR) was used for phenol biodegradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Therefore, biofilm-mediated bioremediation processes are also widely used in wastewater treatment. Coaggregation and biofilm formation has been shown to enhance the phenol tolerance [79][80][81].…”
Section: Comparison Of Biofilm Formation Ability Of the Strains Icp1 And Ictn13 And Their Mixturementioning
confidence: 99%
“…Therefore, biofilm-mediated bioremediation processes are also widely used in wastewater treatment. Coaggregation and biofilm formation has been shown to enhance the phenol tolerance [79][80][81].…”
Section: Comparison Of Biofilm Formation Ability Of the Strains Icp1 And Ictn13 And Their Mixturementioning
confidence: 99%
“…Rotating bed bioreactors, however, can provide some more homogeneity to the contents of the vessel by means of rotation employed. Applications of these systems also include biocatalysis [ 105 , 106 ] and wastewater treatment [ 107 , 108 ], and it has already seen use in mammalian cell culture [ 109 ].…”
Section: Single-use Bioreactors For Stem Cell Biomanufacturingmentioning
confidence: 99%
“…Gürtekin ( 2019) added a zeolite powder to enhance the performance of SBR for the treatment of high strength wastewater especially under low temperature with four cycles performed per day. Pourakbar et al, (2018) reported that attached biofilm is more tolerant to toxic compounds compared to suspended biomass. Yusoff et al, (2016) stated that the inhibitory effect of phenol on the metabolic activities of microorganisms was lowered in hybrid growth systems (including suspended and attached growth systems).…”
Section: Introductionmentioning
confidence: 99%